1994
DOI: 10.1007/bf00341256
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of 12-month outcomes of nursing home patients with aspiration on videofluoroscopy

Abstract: The 12-month clinical outcomes of nursing home patients who underwent videofluoroscopic swallowing evaluation was determined. A retrospective review of 40 patients in a teaching nursing home who had videofluoroscopic swallowing studies from 1987 through 1989 was performed. Clinical outcomes measured included feeding tube placement, rehospitalization within 1 year, prolonged nursing home stay (> 6 months), pneumonia, and pneumonia death. It was determined if outcomes were associated with the presence of aspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(73 citation statements)
references
References 8 publications
1
68
0
3
Order By: Relevance
“…Tube feeding is generally implemented for patients who are severely dysphagic, debilitated, or malnourished and are unable to sustain their caloric and nutritional needs on an oral diet. In our study, tube feeding was significantly associated with aspiration pneumonia, which is consistent with the findings of others [19,28,[31][32][33][34]38,40]. Because our patients were usually not taking any food or liquid by mouth, aspiration presumably occurred with secretions.…”
Section: Variables Significantly Associated With Aspiration Pneumoniasupporting
confidence: 92%
See 1 more Smart Citation
“…Tube feeding is generally implemented for patients who are severely dysphagic, debilitated, or malnourished and are unable to sustain their caloric and nutritional needs on an oral diet. In our study, tube feeding was significantly associated with aspiration pneumonia, which is consistent with the findings of others [19,28,[31][32][33][34]38,40]. Because our patients were usually not taking any food or liquid by mouth, aspiration presumably occurred with secretions.…”
Section: Variables Significantly Associated With Aspiration Pneumoniasupporting
confidence: 92%
“…Since dysphagia predisposes to aspiration, the relationship between dysphagia and aspiration pneumonia might appear obvious, but evidence for this has not always been found [31][32][33]. In fact, several studies of tube-fed patients who are taking no food or liquid by mouth have shown that tube feeding is associated with a higher rate of pneumonia than in patients who are eating [19,23,28,30,31,33,34]. A large body of literature has focused on the association between gastroesophageal reflux and aspiration [18,[35][36][37][38][39][40][41][42].…”
mentioning
confidence: 99%
“…Although feeding recommendations based on VSS have been shown to decrease lower respiratory tract infections in acutely brain-injured adults with dysphagia [30], findings in other studies have suggested that VSS may have an unacceptable false-negative rate in predicting those who will progress to have aspiration pneumonia [32,33]. The reliability of VSS is also variable.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…2 The clinical setting in which pneumonia develops largely distinguishes aspiration pneumonia from other forms of pneumonia.…”
mentioning
confidence: 99%